2009
DOI: 10.1002/joc.1919
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the atmospheric response over southern Africa to SST forcing in the southeast tropical Atlantic and southwest subtropical Indian Oceans

Abstract: ABSTRACT:The sensitivity of the atmospheric circulation and rainfall over southern Africa to various regional sea surface temperature (SST) patterns observed during Benguela Niño events is investigated using an atmospheric general circulation model (AGCM). The model used is the United Kingdom Meteorological Office (UKMO) HadAM3 and experiments using idealizations of observed regional SST anomalies during various Benguela Niño events are performed. It is found that SST forcing in the tropical southeast Atlantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 33 publications
8
35
0
Order By: Relevance
“…Associations between tropical southeastern Atlantic SST and southern African rainfall have been documented (e.g., Hirst and Hastenrath 1983;Nicholson and Entekhabi 1987;Rouault et al 2003;Hansingo and Reason 2009). The strongest relationships tend to occur in late summer [February-April (FMA)], the Angolan wet season, when regional SST reaches its maximum (about 308C).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Associations between tropical southeastern Atlantic SST and southern African rainfall have been documented (e.g., Hirst and Hastenrath 1983;Nicholson and Entekhabi 1987;Rouault et al 2003;Hansingo and Reason 2009). The strongest relationships tend to occur in late summer [February-April (FMA)], the Angolan wet season, when regional SST reaches its maximum (about 308C).…”
Section: Introductionmentioning
confidence: 77%
“…5a). However, as discussed by Rouault et al (2003) and further shown in Hansingo and Reason (2009). 1 in Rouault et al 2003).…”
Section: Circulation Anomaliesmentioning
confidence: 97%
See 1 more Smart Citation
“…Unlike the other regions considered, southern Africa experiences a strong influence from the midlatitudes and important tropical-extratropical interactions (Harrison 1984(Harrison , 1986, which represents an interesting challenge for climate models (e.g., Niznik et al 2015). Modeling southern African climate is also complicated by remote influences, notably from ENSO (Lindesay 1988;Reason et al 2000), the IOD ( Goddard and Graham 1999;Reason 2002), the southwest Indian Ocean dipole (Washington and Preston 2006; Kay and Washington 2008), the southeast Atlantic (Reason et al 2006;Hansingo and Reason 2009), and Antarctica (Reason and Rouault 2005;Pohl et al 2010;Manatsa et al 2013), as well as the role of local land surface interactions, complex orography, and aerosols (Anderson et al 1996;Mason and Joubert 1997;Tyson and Preston-Whyte 2000;Ramanathan et al 2007).…”
Section: Pan-africanmentioning
confidence: 99%
“…Nevertheless, the Congo's significance is increasingly being recognized in scientific literature, not least because anthropogenic‐induced climatic changes have been brought to the forefront of African environmental policy [ James and Washington , ]. Several recent studies have utilized satellite, gauge, and reanalyses data in equatorial Africa to identify controls on both seasonal and interannual rainfall variability, with particular reference to the characteristics of: the African easterly jet [ Nicholson and Grist , ; Dezfuli and Nicholson , ], low‐level westerlies [ Dezfuli and Nicholson , ; Pokam et al ., ], mesoscale convective systems [ Jackson et al ., ], sea surface temperature (SST) teleconnections [ Nicholson and Dezfuli , ; Hirst and Hastenrath , ; Hansingo and Reason , ], and zonal overturning circulations across the region [ Cook and Vizy , ].…”
Section: Introductionmentioning
confidence: 99%